On an image scrambling method via Fibonacci and Lucas numbers - Hakob Sarukhanyan; Grigor Petrosyan (Изд-во НАН РА)
The novel digital image scrambling method based on Fibonacci and Lucas numbers is presented. This scrambling transformation has the following advantages: (a) Encoding and decoding are very simple and can by realized in real-time situations. (b) The scrambling effect is very good, the pixels of the image are re-distributed randomly across the whole image. (c) The method can endure common image attacks, such as compression, noise and loss of data packet.
Keywords: Mathematics; Computer software